Pendampingan tata kelola program dan layanan di Klinik Esther PKBI Sulawesi Utara: Assistance of Program and Service Governance in Esther Clinic of North Sulawesi PKBI North Sulawesi - Angela Fitriani Clementine Kalesaran; Chreisye Kardinalia Fransisca Mandagi; Desi (Sam Ratulangi University, 2024)
Patient satisfaction is very important in the services of a clinic, and for this reason, good management and governance is needed. The implementation of good clinical governance needs to be supported by competent and skilled resources, especially in terms of program and service management at the clinic. Therefore, a community partnership programme was carried out in the form of mentoring with the aim of providing increased knowledge and skills for clinic staff and creating a better management system. The method used is assistance for clinical staff in the form of coordination meetings, workshops, and mediation with related parties where necessary, as well as assistance in developing a better governance system. This activity was carried out for 6 months, from April 2023 to September 2023, with various stages from preparation and implementation to the final stage, namely reporting and dissemination of the results of the activity. The results obtained were an increase in the knowledge and skills of clinical staff as well as better implementation of programmes and service management from partners than before. It is hoped that the programme and service management assistance provided at the Esther PKBI Clinic in North Sulawesi can have a positive impact on partner staff, patients, and the community in general so as to achieve the provision of reliable and innovative health services.